Synthesis and characterization of metal oxides catalyst for production of fame: a comparative study / Najwa Azis, Dr Wan Zuraida and Nur Alwani Ali Bashah - Azis, Najwa; Wan Kamis, Wan Zuraida; Ali Bashah, Nur Alwani (2020)
The accelerating growth and demands in energy consumption, together with growing environmental concerns has sparked renewed attention on the search for an alternative fuel to replace conventional diesel. At present, the pressing awareness on global environmental problem contributed by the burning of fossil fuel as non- renewable energy urge researchers around the world to perform study on biodiesel as an alternative for current world energy sources. Numerous research studies have shown the potential of the usage of heterogenous catalyst in the transesterification process for the production of biodiesel varied through various parameters. Despite the success of numerous heterogenous catalyst in the. industry, Calcium and Chromium based mixed metal oxides catalyst continues to show its promising capability and performance in catalysing the transesterification reaction. In this regard, this research paper presents a comparative approach of synthesis and characterization process of these metal oxides catalyst for production of FAME. The performance of these mixed oxides catalysts was reviewed through its catalytic activity under optimal condition as well as its surface area and pore volume characterization study. This review also includes the recent application of mixed metal oxides catalyst in biodiesel conversion as well its future outlook and suitability for industrial application.